Distributions for time, interspecies and intraspecies extrapolation for deriving occupational exposure limits. Issue 5 (13th March 2022) - Dilger, Marco; Schneider, Klaus; Drossard, Claudia; Ott, Heidi; Kaiser, Eva
Abstract: This work aimed at improving the empirical database of time (i.e., exposure duration), interspecies and intraspecies extrapolation when deriving occupational exposure limits (OELs). For each extrapolation step, a distribution was derived, which can be used to model the associated uncertainties. For time and interspecies extrapolation, distributions of ratios of dose descriptors were derived from studies of different length or species. National Toxicology Program (NTP) study data were manually assessed, and data from REACH (Registration, Evaluation and Authorisation of Chemicals) registration dossiers were evaluated semi‐automatically. Intraspecies extrapolation was investigated by compiling published studies on human toxicokinetic and toxicodynamic variability. A new database was established for toxicokinetic differences in interindividual susceptibility, including many inhalation studies. Using NTP data produced more reliable results than using REACH data. The geometric mean (GM) for time extrapolation subacute/chronic agreed with previous evaluations (GM = 4.11), whereas the GM for subchronic/chronic extrapolation was slightly higher (GM = 2.93) than the GMs found by others. No significant differences were observed between systemically and locally acting substances. Observed interspecies differences confirmed the suitability of allometric scaling, with the derived distribution describing remaining uncertainty. Distributions of intraspecies variability at the 1% and 5% incidence level had medians of 7.25 and 3.56, respectively. When compared with assessment factors (AFs) currently used in the EU, probabilities that these AFs are protective enough span a wide range from 10% to 95%, depending on the extrapolation step. These results help to select AFs in a transparent and informed way and, by allowing to compare protection levels achieved, to harmonise methods for deriving OELs. Abstract : This work aimed at improving the empirical database of time (i.e., exposure duration), interspecies and intraspecies extrapolation. Distributions were derived, which can be used to model the associated uncertainties. When compared with assessment factors (AFs) currently used in the EU, probabilities that these AFs are protective enough span a wide range from 10% to 95%, depending on the extrapolation step. These results help to select AFs in a transparent and informed way and to harmonise methods for deriving OELs.